A Pharmacoinformatic Prediction Model For Adverse Drug Reactions - Omar, Moayyad Jamal Abdel Jabbar Al (2010)

(untitled)
Information technology has become part of all kinds of sciences. Research scientists along with the academicians are seriously thinking about the need of information technology in pharmaceutical sciences including clinical pharmacy and pharmaceutical care. Information technology has been applied indirectly in the medication discovery process and patient care for a long period of time. Pharmacy Informatics involves the study, design, and implementation of information and information systems in Pharmacy. The development of computerized prescriptions and laboratory databases has greatly enhanced the ability of institutions and organizations to screen for known adverse drug reactions (ADR).